A Novel PCR-RFLP Method for Detection of POR28 Polymorphism and its Genotype/Allele Frequencies in a Turkish Population - Ozdemir, Fezile; Oz, Merve Demirbugen; Suzen, Hilat S (Current drug metabolism, 2019)
The Cytochrome P450 (CYP) enzymes are involved in the metabolism of many endogenous and exogenous substances. They need electrons for their activity. CYP mediated oxidation reactions require cytochrome oxidoreductase (POR) as an electron donor. A common genetic variation identified in the coding region of POR gene (POR*28) leads to an alteration in POR activity by causing amino acid change. The current study aimed to determine the allele and genotype frequencies of POR*28 in a healthy Turkish population by using a novel genotyping assay. A novel PCR-RFLP assay was developed for the detection of POR*28 (rs1057868) polymorphism and the obtained frequencies were compared with the data established in various ethnic groups. Genotypic analysis revealed that of 209 healthy, unrelated individuals tested for POR*28 polymorphism, 55.5% of the studied subjects were homozygous for the CC genotype, 34.9% were heterozygous for the CT genotype and 9.6% were homozygous for the TT genotype. The allele frequencies were 0.73 (C) and 0.27 (T). The present results were in accordance with the Hardy- Weinberg equilibrium. The distribution of POR*28 allele varies between populations. The frequency of the T allele among members of the Turkish population was similar to frequencies in Caucasian populations but was lower than in Japanese and Chinese populations. In this study, a novel method was developed, which could be applied easily in every laboratory for the genotyping of POR *28 polymorphism. The developed genotyping method and documented allele frequencies may have potential in understanding and predicting the variations in drug response/adverse reactions in pharmacotherapy and susceptibility to diseases in POR-mediated metabolism reactions.